Investigating hospitality graduates knowledge, skills and abilities using Delphi technique - Mohd Shariff, Nurhazani; Abdul Razak, Roshita; Zainol, Noor Azimin (American Scientific Publishers, 2017)
A specific gap identified from literature on graduates knowledge, skills and abilities showed that none has studied in the context of industry perspectives using Delphi technique.This study used Delphi technique and distributed three rounds survey questionnaires among 16 representatives of four and five star lodging in Peninsular Malaysia. The Delphi analysis ended up with 69 items represent hospitality graduates knowledge, skills and abilities in the context of Malaysian hospitality program.The items were categorized into four domains namely Workplace, Academic, Management and Personal Effectiveness.The study highly contributes to the implementation of Delphi technique as effective tool in determining the graduates knowledge, skills and abilities. Further, it also assists the academic institutions specifically in Malaysia by strengthening the foundation of hospitality curriculum taking into account the four identified domains.